2021
DOI: 10.1007/s12594-021-1873-1
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Rainfall Variability to Flood Risk: A Case Study of the Ghaggar River Basin

Abstract: Floods are the most common natural disasters influenced by climatic variables and anthropogenic activities. Ghaggar is a seasonal river of north-western region of India and this basin has been experiencing moderate to high intensity of floods frequently. The present study aims to find out the impact of the rainfall variability on the flooding scenario of this basin using hydrometeorological data. The rainfall data was collected for 12 stations of the basin. The rainfall and extreme rainfall of the Ghaggar basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…There is a seasonal river in the northwestern district of India named Ghaggar, which regularly suffers from reasonable to large concentrations of torrents. Recently, Gorai et al (2021) reported that inconsistency in rainfall influences the flooding situation of this basin. This study was carried out using hydrometeorological data.…”
Section: Introductionmentioning
confidence: 99%
“…There is a seasonal river in the northwestern district of India named Ghaggar, which regularly suffers from reasonable to large concentrations of torrents. Recently, Gorai et al (2021) reported that inconsistency in rainfall influences the flooding situation of this basin. This study was carried out using hydrometeorological data.…”
Section: Introductionmentioning
confidence: 99%